Systematic Literature Review Analysis of the Utilization of Artificial Intelligence on the Quality of Healthcare Services in Indonesia Frieska Piesesha - Piesesha, Frieska; Wibowo, Bima Ardiyanto (Indonesian Journal of Medical Sciences and Public Health, 2025)
Digital transformation in the health sector has accelerated the adoption of Artificial Intelligence (AI) as a strategic innovation to improve the quality of healthcare services. AI has the capability to process large volumes of health data quickly and accurately, thereby supporting clinical decision-making, enhancing service efficiency, and improving patient safety. However, the implementation of AI in Indonesia still faces several challenges, particularly related to the readiness of human resources, infrastructure limitations, data security, and ethical and regulatory issues. This study aims to analyze the role of Artificial Intelligence in improving the quality of healthcare services in Indonesia based on a review of recent literature. The research employed a literature review method with a systematic review approach guided by the PRISMA framework. Literature searches were conducted using PubMed, ScienceDirect, and Google Scholar databases, focusing on articles published between 2020 and 2025. Out of 3,380 identified articles, five studies met the inclusion and exclusion criteria and were selected for further analysis. The findings indicate that the implementation of AI contributes positively to the improvement of healthcare service quality, particularly in terms of effectiveness, efficiency, patient safety, and timeliness of care. AI enhances diagnostic accuracy, supports clinical decision-making, optimizes administrative and clinical processes, and improves the quality of nursing care through real-time patient monitoring and more accurate documentation. Nevertheless, the implementation of AI remains constrained by limited healthcare workforce competencies, inadequate technological infrastructure, and concerns related to data security, privacy, and regulatory frameworks. In conclusion, Artificial Intelligence holds significant potential as a strategic instrument for improving the quality of healthcare services in Indonesia. Optimizing the use of AI requires strengthening human resource capacity, developing adequate technological infrastructure, and establishing clear policies and regulations to ensure the ethical, secure, and sustainable application of AI in healthcare services.